2019
DOI: 10.1080/09669582.2019.1606815
|View full text |Cite
|
Sign up to set email alerts
|

Understanding visitor–resident relations in overtourism: developing resilience for sustainable tourism

Abstract: While almost all travel destinations seek to increase tourists, less attention is paid to balancing the growth in tourists against consequent visitor-resident irritants, which is essential if the objective is to make tourism more sustainable. Overlooking the carrying capacity of a destination is a common mistake committed when formulating travel visa policies. Overtourism is a term recently used to contextualize this potential hazard to many popular tourist destinations worldwide. One notable case in point is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(96 citation statements)
references
References 61 publications
(59 reference statements)
3
85
0
8
Order By: Relevance
“…In contrast, tourism activity can increase the local cost of living, contribute to the increase in noise pollution, agglomeration, traffic, crime problems, contributing to the decrease in the residents' well-being. In addition to the assessment related to the subjective well-being perceived by residents, the concept of overtourism is also directly related to how much the destination can deal effectively with the social and environmental effects generated by the tourist activity in its territory [2,34].…”
Section: Subjective Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, tourism activity can increase the local cost of living, contribute to the increase in noise pollution, agglomeration, traffic, crime problems, contributing to the decrease in the residents' well-being. In addition to the assessment related to the subjective well-being perceived by residents, the concept of overtourism is also directly related to how much the destination can deal effectively with the social and environmental effects generated by the tourist activity in its territory [2,34].…”
Section: Subjective Well-beingmentioning
confidence: 99%
“…Thus, when the adverse effects of the tourist activity outweigh the benefits generated by the activity, a negative feeling may arise in the residents regarding the development of tourism in their destination [1,40,41]. Overtourism has been considered one of the greatest threats to global tourism development [34,42].…”
Section: Overtourismmentioning
confidence: 99%
“…When over-tourism occurs, residents experience its side effects in environmental, economic, and social aspects, whereas tourists experience a decrease in visit satisfaction due to crowding, and a lower likelihood of return visits [3][4][5]. Irresponsible use of resources due to tourism development has led to conflicts between tourists and locals, creating difficulties in sustainable tourism [6]. Side effects from over-tourism have been reported around the world, and solutions are being sought [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors suggested activities to galvanise winter tourism and/or support the summer season on the basis of economic sustainability, for example, considering the snowmaking issues [10][11][12] or defining adaptation strategy plans [13][14][15]. Some others underlined that eco-tourism and natural heritage in mountain areas can be considered important alternatives to incoming sources and stimulate new opportunities [16,17].When taking into account the Alps, tourism is an outstanding phenomenon-with about 120 million tourists per year [18], the Alps are one of the most visited mountain ranges in the world.Arrivals and presences in the Alps, however, vary from destination to destination; in some alpine valleys, tourism is so developed that is starting to create concerns around its environmental and social implications due to over tourism [19,20]. On the other hand, some alpine valleys, which do not have renewed hallmarks, are not popular even if the local context would be able to provide guests with an interesting tourist offer.…”
mentioning
confidence: 99%
“…Arrivals and presences in the Alps, however, vary from destination to destination; in some alpine valleys, tourism is so developed that is starting to create concerns around its environmental and social implications due to over tourism [19,20]. On the other hand, some alpine valleys, which do not have renewed hallmarks, are not popular even if the local context would be able to provide guests with an interesting tourist offer.…”
mentioning
confidence: 99%